2010
DOI: 10.1021/ma902670q
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers as Drug Carriers: Dynamics of PEGylated and Methotrexate-Loaded Dendrimers in Aqueous Solution

Abstract: An investigation of the dynamics of aqueous solutions of PEG, PEGylated dendrimers, methotrexate, and PEGylated and drug (methotrexate)-loaded dendrimers was carried out with broadband dielectric relaxation spectroscopy (DRS). Two dielectric dispersions were observed in all systems, and the explanation of their molecular origin was offered. The lower frequency process, characterized by an activation energy of 52.2 kJ/mol, was attributed to motions in ice. The higher frequency process is of the Cole−Cole type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This class of biopolymers is also concerned by the previously mentioned general trends. Some successful attempts undertaken to design new dendritic polypeptide-like molecules as well as other water soluble dendrimers (for instance well-known poly(amido amine) (PAMAM)) had demonstrated the benefits of turning the shape and surface properties of such structurally ordered macromolecules [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This class of biopolymers is also concerned by the previously mentioned general trends. Some successful attempts undertaken to design new dendritic polypeptide-like molecules as well as other water soluble dendrimers (for instance well-known poly(amido amine) (PAMAM)) had demonstrated the benefits of turning the shape and surface properties of such structurally ordered macromolecules [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…PEO, as a water-soluble polymer, was also used in the pharmaceutical field. It was reported that the encapsulation efficiency increased and the release rate was slowed down by attaching PEO chains. To decrease water solubility of PAA, novel interpolymer complexes of PAA and methoxy PEO with various molecular weights and compositions, which can promote the adhesive process and slow down the dissolution rate, were prepared. Therefore, it is important to obtain the internal dynamics in PAA- g -PEO solution for its potential application. The interchain interaction of PAA- g -PEO in aqueous solution has been investigated using laser light scattering (LLS), viscometry, and rheological measurements .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a proper modification of dendrimer ends could consist of attaching end groups that are (highly) incompatible with the “main dendrimer”. For instance, in PEGylated dendrimers, there are virtually no contacts between terminal polyethylene glycol (PEG) spacers and the dendrimer interior, and this dendrimer has a good perspective of practical applications for drug delivery …”
Section: Introductionmentioning
confidence: 99%
“…For instance, in PEGylated dendrimers, there are virtually no contacts between terminal polyethylene glycol (PEG) spacers and the dendrimer interior, 22 and this dendrimer has a good perspective of practical applications for drug delivery. 23 The properties of the G = 4 generation carbosilane dendrimer with terminal cyanobiphenyl mesogenic groups in dilute chloroform solution were studied in ref 24 at different temperatures. Comparison of the mobility of terminal and inner CH 3 groups at 300 K and lower temperatures allowed the authors to suggest that the density in the dendrimer interior is lower than that at the periphery.…”
Section: Introductionmentioning
confidence: 99%